2017
DOI: 10.1371/journal.pone.0168804
|View full text |Cite|
|
Sign up to set email alerts
|

Patterns of Multiple Risk Exposures for Low Receptive Vocabulary Growth 4-8 Years in the Longitudinal Study of Australian Children

Abstract: Risk exposures and predictions of child development outcomes typically estimate the independent effects of individual exposures. As a rule though, children are not exposed piecemeal to individual or single risks but, rather, they are exposed to clusters of risk. Many of these clusters of risks are better thought of as comprising a developmental “circumstance” with a substantial duration, over which period, additional risk exposures also accumulate. In this paper we examined the distribution of 16 single risk e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 22 publications
5
29
0
Order By: Relevance
“…The High needs family group was the largest group and accounted for 22% of the sample. Although risks were not the same, similar complex multiple risk groups have been identified in other LCA studies and have been found to be associated with poor child neurodevelopment . It is unsurprising that a multiple need group was identified in our cohort given the complex number of factors that can influence child neurodevelopment.…”
Section: Commentsupporting
confidence: 72%
See 1 more Smart Citation
“…The High needs family group was the largest group and accounted for 22% of the sample. Although risks were not the same, similar complex multiple risk groups have been identified in other LCA studies and have been found to be associated with poor child neurodevelopment . It is unsurprising that a multiple need group was identified in our cohort given the complex number of factors that can influence child neurodevelopment.…”
Section: Commentsupporting
confidence: 72%
“…To date, LCA has been used to describe the combination of risk factors and their association with early child neurodevelopment in only a handful of studies . However, only two of these studies have investigated differences within ethnic groups .…”
Section: Introductionmentioning
confidence: 99%
“…Similar to previous findings exploring risk clusters with quantitative methodology (Christensen et al . 2017), this case‐based study demonstrated there was no one risk or protective condition that was necessary for Good or Poor language outcomes and all were sufficient in a variety of paths and patterns. Similarly, the paths to Good language were dominated by protective factors and Poor language by risk factors (Christensen et al .…”
Section: Discussionmentioning
confidence: 73%
“…2013, Christensen et al . 2017). The languages used in the home were collected by parent report at birth and when the child was 18 and 32 months.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation